Tuberculosis in HIV/AIDS patients - Mendoza Ticona, Alberto (2018)
Tuberculosis (TB) and the human immunodeficiency virus (HIV) infection are epidemiologically linked with respect to their risk prognosis, be it for the development of TB in an HIV-infected patient or as a prognostic indicator of HIV infection. The association of TB and HIV potentiates the aggressiveness of both.The extension of HIV epidemics all over the world allowed that its interaction with tuberculosis modified the descending curve of the frequency of TB in those countries that had achieved such reduction, such as the USA. In developing countries highly endemic for TB, this interaction worsened this problem. The risk of dying because of TB in an HIV-infected patient is 2 to 4 times higher compared to that in a TB patient not infected with HIV, independently of the CD-4 lymphocyte count.